PREVALENCE AND DETERMINANTS OF INTERNET ADDICTION AMONG YOUTH IN MALAYSIA - Nor Auni Athirah Mohd Azmi; Nor Allysa Ismail; Rozalieya Mazlan; Nurul Aqilah Ramaherwanto; Siti Anisya Jaffri; Siti Mariam Ali (International Journal of Accounting, Finance and Business, 2022)
This paper aims to determine the issue of internet addiction and to identify thedeterminants of internet addiction among youth. The current study reviewed research articlesthat were gathered from ACM, Google Scholar and Science Direct. A total of 15 articles havebeen reviewed from 2003 to 2022. This research has been classified into internet addiction,determinants of internet addiction, followed by definition related to internet addiction amongyouth. It was observed that the risk factors of internet addiction affected various type ofproblems among youth. The findings also reveal that internet addiction types include onlinegaming, social media, online gambling, online shopping, and information overload. Based onthe reviews, the common determinants of internet addiction were identified, including familyrelationships, psychological factors, social media, excessive gaming, and entertainment toolsfor youth. This paper also helps to understand the definition and the determinants of internetaddiction also its impact among young people. Internet addiction control management can beconducted among youth on a regular basis where we can educate them about how to managethe time wisely and they can do other things that will give them benefits. A total of 15 researcharticle on internet addiction are reviewed in this study which will be guideline for the policymakers in offering the preventive measures for the youth. Besides, the paper is classified basedon major factors influence on internet addiction among youth.